If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 10)(x + 6) = -12x Reorder the terms: (10 + 2x)(x + 6) = -12x Reorder the terms: (10 + 2x)(6 + x) = -12x Multiply (10 + 2x) * (6 + x) (10(6 + x) + 2x * (6 + x)) = -12x ((6 * 10 + x * 10) + 2x * (6 + x)) = -12x ((60 + 10x) + 2x * (6 + x)) = -12x (60 + 10x + (6 * 2x + x * 2x)) = -12x (60 + 10x + (12x + 2x2)) = -12x Combine like terms: 10x + 12x = 22x (60 + 22x + 2x2) = -12x Solving 60 + 22x + 2x2 = -12x Solving for variable 'x'. Reorder the terms: 60 + 22x + 12x + 2x2 = -12x + 12x Combine like terms: 22x + 12x = 34x 60 + 34x + 2x2 = -12x + 12x Combine like terms: -12x + 12x = 0 60 + 34x + 2x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(30 + 17x + x2) = 0 Factor a trinomial. 2((15 + x)(2 + x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(15 + x)' equal to zero and attempt to solve: Simplifying 15 + x = 0 Solving 15 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + x = 0 + -15 x = 0 + -15 Combine like terms: 0 + -15 = -15 x = -15 Simplifying x = -15Subproblem 2
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Solution
x = {-15, -2}
| 15w-6w-8w+7=32 | | 14d+12d-20d-4d-1=21 | | -20-14d+20=20-16d | | 38x-15=20x | | 97*2= | | 8[3-(5+2x)]-2x=-18+2(1-9x) | | 3xa+2x=-7 | | -23s+19s+40=0 | | 9-6/12=a-2/4 | | 12m+5=56 | | 3/2=x-5/2 | | 8-2(7x-3)=1 | | .5x+3=6x-8 | | -5b-b+15b-10b+-12=4 | | y=4(5x+5)+12 | | 5-25b=10 | | -10p-16p+8p+15p+8=-7 | | 90-(3+9)*7= | | cos(65)=(7/x) | | 5x^2=900 | | .4x+3.91=21.05 | | 30+y+x=180 | | 16t-7t-8t-t+t+2=16 | | 12=n/9=1 | | 2x-14y=-22 | | 3(2t-6)=2(3r-9) | | 5x+5(4x+12)=10 | | 2(x-3)=1/2x | | 3(n+1)-2n=0 | | -2z+13z+13z-20z=-20 | | 0=4+2n | | 13+b=-4 |